NUMERICAL METHOD FOR ESTIMATION OF TENSILE LOAD IN TIE-RODS - Kseniia Riabova; Luca Collini; Rinaldo Garziera (Acta Polytechnica CTU Proceedings)
The work introduces a two-phase method for determination of axial loads in tie-rods. The method described here consists of an experimental activity and an automated numerical calculation. The influence of considering an elastic Winkler-type bed to model the tie-rod constraint inside the wall has been investigated. The algorithm used for calculation involves a solution of a functional minimization problem, where the tensile load and the stiffness of elastic foundation at the edges are used as optimization parameters and the error function, which describes the deviation between the frequencies measured and those calculated using finite element method, is minimized. Qualitative analysis of the results showed a significant reduction of the error compared to models with different boundary conditions. The method showed to be conservative for the strength evaluation of the rods, because the optimal values of tensile loads appeared to be higher than the load in perfect encastre conditions.